Pembelajaran Peluang Bisnis di Bulan Ramadhan pada Mahasiswa di Surabaya - Hapsari Shinta Citra Puspita Dewi; Nur Shanti Retno Pembayun; Dwi Cahyo Kartiko (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2026)
This community engagement program focuses on strengthening students’ entrepreneurial capacity by utilizing the economic momentum of the Ramadan season. As a month filled with religious traditions, cultural practices, and dynamic social activities, Ramadan creates significant shifts in consumer behavior, resulting in increased demand for iftar snacks, seasonal markets, and various short-term business opportunities. These conditions provide students with an accessible space to learn about opportunity recognition, basic business management, and practical marketing strategies tailored to the needs of the surrounding community. Through training sessions, surveys, field practice, and evaluations, students gain hands-on experience that enhances their creativity and innovation, allowing them to develop products and services relevant to the local market. Cultural values also play a central role, as local traditions help shape students’ business ideas and strengthen their understanding of consumer preferences. The collaboration between students, UMKM partners, and community members facilitates knowledge transfer, expands entrepreneurial networks, and supports local economic empowerment. The overall results demonstrate that structured guidance, cultural integration, and active participation in Ramadan activities significantly contribute to students’ entrepreneurial development. Therefore, Ramadan-based entrepreneurship learning can serve as an effective model for fostering young entrepreneurs who are adaptive, innovative, and capable of contributing to sustainable community development.